Factors Influencing the Social Nature of Religion and Religious Extremism - Jamalov, Mubariz (Scholarya Demo Journal of Ruby, 2019)
Religion has existed in the individual and social life of human throughout history. This is the most obvious indicator of the social structure of religion. As religion has an impact on society, the influence of social events is also observed. This article examines the effects of factors on religion such as social change, globalization, modernism and secularism and the consequent reactions of religious communities. The factors that influence religion often lead to the emergence and spread of extremism. Therefore, change is not always welcomed. Those who see change as destruction, choose the path bound to the roots of religion. This leads to radicalism and extremism. Therefore, when we look at history, we can see that religious extremism coincides with the change period. In this case, we observe that religion or religious societies take different positions. This leads to the emergence of various religious trends and approaches. It is possible to divide these trends and concepts into two groups: traditionalists and innovators. Radical trends stem from this together with different manifestations of the traditionalist approach. Basically, radicalism is about choosing the root when faced with changes. This in some cases leads to extremism. Thus, it is possible to speak about the formation of the line of social change-traditionradicalism-extremism in the cause-and-effect chain.